PERENCANAAN POLA PERJALANAN WISATA KECAMATAN SIAK KABUPATEN SIAK - Ivan Juan Daniel; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Siak District has a good tourism potential, with the culture and history of the Siak Sri Indrapura Kingdom included in it. The Siak Sri Indrapura Kingdom’s heritage is very fascinating because it’s not only a great site to be a destination, but also a valuable place to research. Coupled with artificial tourism made by the Regional Government of Siak Regency, which make it an additional value for Siak District Tourism. Therefore, this research was conducted to determine its tourist destinations alongside their attractions, amenities, accessibility and ancillary in Siak District. This study also aims to plan a travel pattern and recommend it. This study used a descriptive qualitative method. While the data collection techniques in this study used literature study, observation, interviews and documentation. The results of this study will bring out into the open about tourist destinations and their attractiveness, accessibility, amenities and ancillary in Siak District, as well as designing the travel patterns in Siak District. Keywords: Tourism, Travel Patterns, Siak District, Siak Sri Indrapura